Gaya Hidup Berbasis Digital Dan Perilaku Konsumtif Pada Gen Z Di Bandar Lampung: Keputusan Pembelian Melalui Marketplace Shopee - Nurmalia, Gustika; Mutiasari Nur Wulan; Zathu Restie Utamie (Jurnal Rekoginisi Ekonomi Islam, 2024)
In the current era of modern society dominated by Gen Z, along with the development of digital trends, people's lifestyles are slowly changing, tending to prefer things that are fast, easy and practical that can be done via smartphone. The problem formulation in this research is whether a digital-based lifestyle influences purchasing decisions on the Shopee marketplace? Does consumer behavior influence purchasing decisions on the Shopee marketplace? And do digital-based lifestyles and consumer behavior together influence purchasing decisions on the Sahopee marketplace from an Islamic economic perspective? The aim of this research is to find out whether a digital-based lifestyle influences purchasing decisions on the Shopee marketplace and to find out whether consumer behavior influences purchasing decisions on the Shopee marketplace. This research uses a quantitative type of research. The research was conducted in the city of Bandar Lampung, the population in this study was Gen Z in Bandar Lampung, the sample used in this study was 96 people taken using purposive sampling techniques, a questionnaire that had been tested for validity and reliability, and the data analysis technique used was hypothesis testing. The type of data in this research is primary data, data was collected via Google form and analyzed using the Multiple Linear Regression Analysis technique using the SPSS program. The results of this research show that lifestyle (X1) has a positive and significant effect on purchasing decisions. This means that every time there is an improvement in lifestyle, it will increase consumer purchasing decisions. This happens because of changes in increasingly modern times so that people compete to follow lifestyle trends. Then, consumer behavior (X2) has a positive and significant effect on purchasing decisions. This means that the higher the consumer behavior in generation Z, the higher the level of purchasing decisions. Generation z tends to be highly influenced by social factors and trends. Shopee, as an e-commerce platform that is popular among them, often displays the latest trends, viral products, and limited special offers. And provides easy and practical accessibility for generation z in Bandar Lampung. By using a smartphone and an internet connection, they can search, compare and buy the products they want. This makes it easier for them to fulfill their consumption needs and desires.